1991
DOI: 10.1080/03601239109372746
|View full text |Cite
|
Sign up to set email alerts
|

Bildung und abbau von triadimenol nach anwendung von triadimefon in einer weizenmonokultur

Abstract: During two vegetation periods, the behaviour of the triadimefon metabolite, triadimenol, in different plant parts of winter wheat and in soil was investigated. The fungicide Bayleton DF (triadimefon + captafol) was applied at the beginning of earing. Different ratios of triadimenol-A/-B were found in individual plant parts. Triadimenol-A predominated in the two uppermost leaves, and triadimenol-B in the roots and in the soil. No residues of triadimenol were found in grain at harvest time (detection limit 0.01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At present, studies have shown that the degradation rate of five pesticides in crops is fast, which belongs to degradable pesticides. [21][22][23][24][25] In this study, we used QuEChERS method combined with high-performance liquid chromatography (HPLC) and gas chromatography (GC) to further study the effects of temperature and humidity on the degradation rates of the five pesticides under storage conditions. The results from monitoring pesticide residue could offer insight into the design of government pesticide control and risk management programs for corn flour or other grains in future.…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies have shown that the degradation rate of five pesticides in crops is fast, which belongs to degradable pesticides. [21][22][23][24][25] In this study, we used QuEChERS method combined with high-performance liquid chromatography (HPLC) and gas chromatography (GC) to further study the effects of temperature and humidity on the degradation rates of the five pesticides under storage conditions. The results from monitoring pesticide residue could offer insight into the design of government pesticide control and risk management programs for corn flour or other grains in future.…”
Section: Introductionmentioning
confidence: 99%